Epistemologi Ibnu Rusyd (Telaah Relasi Wahyu dan Rasio) - Muslikhul Ibad; Ahmad Dwi Nur Khalim (AN NUR: Jurnal Studi Islam, 2022)
This article was written with the aim of examining Ibn Rushd's thoughts in bringing together religion and philosophy. Ibn Rushd views that there was a peaceful relationship between sharia and philosophy because apart from placing the two as a means of achieving the truth and affirming that they supported each other, not deny each other in the form of the principle of unification. That means, both were in one goal, namely to find the truth. The research method used by the author was library research. While the results of the study explained that in Ibn Rushd's view, to bring together philosophy and religion, a tool was needed, namely the mind. Ibn Rushd gave his own area of ??work on revelation and the intellect (ratio) and tried to link the two through his theory of takwil. Takwil was used to bridge the difference between the meaning of textuality and rational understanding.